Delocalisation and Psychosocial Wellbeing of Public Secondary School Principals in Selected Counties in Eastern Region, Kenya - Stephen, Munyiri; Ogembo, John; Susan, Kinyua (Advances in Social Sciences Research Journal, 2022)
The Teachers Service Commission proposed and implemented Delocalisation policy among the teaching fraternity in Kenya since 2017 beginning with Principals of Secondary schools and Head teachers of Primary schools. Aimed at giving a national outlook to the management of educational institutions in the country, enhancing cohesion and quality of their management, implementation of the policy has been met with mixed reactions. While proponents link its implementation with improved institutional management, critics have suggested that the implementation be scrapped due to what they allege are its adverse effectss on Principals and Head teachers. Especially said to be adversely affected are the psychosocial wellbeing of delocalised Principals and Head teachers. This means that implementation of the policy could be adversely affecting the mental and social health of these personnel. However, empirical literature that could directly link the adverse psychosocial effects to implementation of the policy is still limited. This study therefore set out to establish the relationship between delocalisation process and the psychosocial wellbeing of school administrators with a specific focus on delocalised Public secondary school Principals in selected Counties in Eastern region in Kenya. A descriptive cross-sectional survey was formulated for the study. Data was collected from 277 delocalised Principals, 12 Education officials and 18 Union officials using questionnaires. Data obtained was analysed descriptively and inferentially to put forward recommendations. Findings showed a significant negative relationship between delocalisation process and psychosocial wellbeing of the delocalised Principals implying adverse effect of the process on delocalised Principals’ psychosocial wellbeing. The relationship was found to be stronger on older Principals compared to relatively younger ones. At the same time, it was established that the effect was dependent on type of school, Principal delocalised to national and extra county schools having a more positive view on the process compared to those delocalised to County and Sub-County schools. It is therefore recommended that implementation of the process take a cautious humane approach to minimise its adverse effects.